Improvements in an Organization's Culture of Health Reduces Workers' Health Risk Profile and Health Care Utilization. Issue 2 (February 2019) - Henke, Rachel Mosher; Head, Michael A.; Kent, Karen B.; Goetzel, Ron Z.; Roemer, Enid Chung; McCleary, Katherine
Abstract : Objective: To examine changes in internal and external cultures of health scores and relate those changes to employees' health risks, health care utilization, and costs for 21 large employers ( N = 641, 901). Methods: We measured the relationship between changes in internal and external culture of health scores and changes in employee health risks, health care utilization, and costs. Results: Improvements in a company's internal culture of health predicted lower levels of obesity, poor diet, and tobacco use but higher stress for employees reporting high baseline risk. For those not at high baseline risk, health improved for depression, alcohol consumption, and diet. Improvements in internal culture of health also led to lower prescription drug utilization. Conclusion: Investments in internal culture of health predict improvements in some employee health risks and health care utilization. Abstract : Supplemental Digital Content is available in the text